Back in business industrial policy for emerging economies in the new globalization. - Berglof,Erik (Economics Working Papers., 2018)
Todays emerging economies face a dual structural transformation challenge: (i) to move closer to the current world technology frontier (traditional catch-up), and (ii) to adjust to technological change in advanced economies and increasingly binding environmental and social constraints. They must do so subject to their available state capacity. The paradox of industrial policy is that it is most straightforward when state capacity is the most constrained. In this paper, the authors suggest that emerging economies still should explore sector based horizontal policies addressing market and state failures in individual industries.